2017
DOI: 10.1007/s11368-017-1706-4
|View full text |Cite
|
Sign up to set email alerts
|

Methodological perspectives on the application of compound-specific stable isotope fingerprinting for sediment source apportionment

Abstract: Compound-specific stable isotope (CSSI) fingerprinting of sediment sources is a recently introduced tool to overcome some limitations of conventional approaches for sediment source apportionment. The technique uses the C-13 CSSI signature of plant-derived fatty acids (delta C-13-fatty acids) associated with soil minerals as a tracer. This paper provides methodological perspectives to advance the use of CSSI fingerprinting in combination with stable isotope mixing models (SIMMs) to apportion the relative contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 141 publications
0
42
0
Order By: Relevance
“…Other tracers as compound-specific stable isotopes may offer potential to further discriminate among vegetation covers. This technique has been successfully tested in recent research to discriminate land uses as sediment sources (Alewell, Birkholz, Meusburger, Schindler Wildhaber, & Mabit, 2016;Blake, Ficken, Taylor, Russell, & Walling, 2012;Upadhayay et al, 2017) in different parts of the world.…”
Section: Spatial Patterns Of Soil Redistributionmentioning
confidence: 99%
“…Other tracers as compound-specific stable isotopes may offer potential to further discriminate among vegetation covers. This technique has been successfully tested in recent research to discriminate land uses as sediment sources (Alewell, Birkholz, Meusburger, Schindler Wildhaber, & Mabit, 2016;Blake, Ficken, Taylor, Russell, & Walling, 2012;Upadhayay et al, 2017) in different parts of the world.…”
Section: Spatial Patterns Of Soil Redistributionmentioning
confidence: 99%
“…These plant lipids are continuously transferred into the soil after their production, through litter deposition and abrasion of cuticular waxes (Glaser, 2005;Jansen and Wiesenberg, 2017). Compound-specific isotope analysis (CSIA) of lipid constituents such as long-chain fatty acids and n-alkanes has been routinely used as a valuable tool to infer soil OM source and turnover (Wiesenberg et al, 2004;Zocatelli et al, 2012), reconstruct paleoenvironments and paleovegetation (Glaser and Zech, 2005;Eglinton and Eglinton, 2008), and fingerprint sediment-bound OM sources in freshwater and marine environments (Canuel et al, 1997;Galy et al, 2011). As freshwater ecosystems are currently under the threat of high sediment input due to the intensification of anthropogenic activities and associated land-use changes, the CSIA technique has recently been adopted for improved quantification of the sediment sources from different land uses (Gibbs, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Alewell et al (2016) proposed and used long-chain FAs for source apportionment. Data from other published studies (e.g., Blake et al, 2012;Hancock & Revill, 2013) applied short-chain FAs for which isotopic composition is considered to be non-conservative due to degradation and in situ production by microorganisms in soil and aquatic systems (Reiffarth et al, 2016;Upadhayay et al, 2017). Indeed, unpublished FA content data of Blake et al (2012) showed that short-chain (C 16 and C 18 ) sediment FA contents were an order of magnitude greater than in the soil source, questioning the selected tracer reliability in this study (Reiffarth et al, 2016).…”
Section: Revisiting Published Datamentioning
confidence: 99%
“…Using an IMM to unravel a mixture using isotopic tracers thus provides a proportional contribution of the sources to the isotopic tracer in the mixture, while it is the proportional contribution of the source to the sediment mix itself, which is of interest for apportionment studies. The relationship between π n,s and the source proportion P s is given by πn,s=Ps×Cn,ss=1SPs×Cn,s with C n,s being the content of the isotopic tracer n in source s (Upadhayay et al, ).…”
Section: Introductionmentioning
confidence: 99%